Estimation de la contribution de la production potagère domestique au système alimentaire local - Maxime Marie (VertigO, 2019)
The paper explores the contribution of domestic gardening to the local food systems in three cities of the North-West of France : Rennes, Caen, and Alençon. The methodology of this research is based on a fine-scale inventory of vegetable gardening space and on a survey with gardeners cultivating a vegetable garden. The results show that the areas dedicated to domestic production, although often underestimated, are very important (nearly 45 ha in Rennes, a little more than 50 ha in Caen and about 25 ha in Alençon). This work shows also the central place of home gardens cultivated in the private gardens of houses within the total vegetable areas. Their spatial distribution is not homogeneous and accounts for the effects of urban morphology and the social composition of neighborhoods. We also note that the cities most marked by the presence of popular categories and retirees are those where the areas of vegetable gardens per household are the most important. Finally, an evaluation of the contribution of domestic gardening production to the local food system has been done. It shows that this contribution is differentiated according to cities and neighbourhoods, due to several parameters : the social composition of the population, urban morphology and access to a cultural space.